Multinodular and vacuolating neuronal tumors in epilepsy: dysplasia or neoplasia?. (19th September 2017) - Thom, Maria; Liu, Joan; Bongaarts, Anika; Reinten, Roy J.; Paradiso, Beatrice; Jäger, Hans Rolf; Reeves, Cheryl; Somani, Alyma; An, Shu; Marsdon, Derek; McEvoy, Andrew; Miserocchi, Anna; et al.
Abstract: Multinodular and vacuolating neuronal tumor (MVNT) is a new pattern of neuronal tumour included in the recently revised WHO 2016 classification of tumors of the CNS. There are 15 reports in the literature to date. They are typically associated with late onset epilepsy and a neoplastic vs. malformative biology has been questioned. We present a series of ten cases and compare their pathological and genetic features to better characterized epilepsy‐associated malformations including focal cortical dysplasia type II (FCDII) and low‐grade epilepsy‐associated tumors (LEAT). Clinical and neuroradiology data were reviewed and a broad immunohistochemistry panel was applied to explore neuronal and glial differentiation, interneuronal populations, mTOR pathway activation and neurodegenerative changes. Next generation sequencing was performed for targeted multi‐gene analysis to identify mutations common to epilepsy lesions including FCDII and LEAT. All of the surgical cases in this series presented with seizures, and were located in the temporal lobe. There was a lack of any progressive changes on serial pre‐operative MRI and a mean age at surgery of 45 years. The vacuolated cells of the lesion expressed mature neuronal markers (neurofilament/SMI32, MAP2, synaptophysin). Prominent labelling of the lesional cells for developmentally regulated proteins (OTX1, TBR1, SOX2, MAP1b, CD34, GFAPδ) and oligodendroglial lineage markers (OLIG2, SMI94) was observed. No mutations were detected in the mTOR pathway genes, BRAF, FGFR1 or MYB . Clinical, pathological and genetic data could indicate that MVNT aligns more with a malformative lesion than a true neoplasm with origin from a progenitor neuro‐glial cell type showing aberrant maturation.